2016
DOI: 10.1021/jacs.5b13214
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystal and Electronic Structure of a 1.3 nm Indium Phosphide Nanocluster

Abstract: Magic-sized nanoclusters have been implicated as mechanistically relevant intermediates in the synthesis of group III-V quantum dots. Herein we report the single-crystal X-ray diffraction structure of a carboxylate-ligated indium phosphide magic-sized nanocluster at 0.83 Å resolution. The structure of this cluster, In37P20(O2CR)51, deviates from that of known crystal phases and possesses a non-stoichiometric, charged core composed of a series of fused 6-membered rings. The cluster is completely passivated by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

35
325
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(361 citation statements)
references
References 47 publications
35
325
1
Order By: Relevance
“…Cossairt and co-workers have recently shown that carboxylic acids bind to InP nanoclusters in 4 modes, one of which involves symmetric bridging of two indium atoms. 63 If this bridging binding mode is also present for native oleate ligands on CdSe, the increased coverage of thiol ligands could result from displacement of carboxylic acids binding in this bridging motif. In order to maintain charge balance in these various ligand exchange processes, the ligands binding to open coordination sites are likely doing so as neutral thiols, while those displacing the native oleate ligands undergo a proton transfer reaction and bind as thiolates.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…Cossairt and co-workers have recently shown that carboxylic acids bind to InP nanoclusters in 4 modes, one of which involves symmetric bridging of two indium atoms. 63 If this bridging binding mode is also present for native oleate ligands on CdSe, the increased coverage of thiol ligands could result from displacement of carboxylic acids binding in this bridging motif. In order to maintain charge balance in these various ligand exchange processes, the ligands binding to open coordination sites are likely doing so as neutral thiols, while those displacing the native oleate ligands undergo a proton transfer reaction and bind as thiolates.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…Thes ynthesis was carried out at 100 8 8C, at emperature at which the cluster does not spontaneously thermally decompose (t 1/2 > 5h at 150 8 8C), but where any added P(SiMe 3 ) 3 immediately reacts,t hus allowing for aq uantitative relation between the equivalents of P(SiMe 3 ) 3 added and the evolution of the NCs via their optical spectra. Closer inspection of the optical change versus time (Figure 1, inset) reveals that the growth occurred across three distinct regimes.Regime Iis an apparent induction period wherein the optical spectra show no appreciable shift, slowly accelerating by the addition of approximately 5equivalents of P(SiMe 3 ) 3 .G iven that the lowest energy cluster transitions have been previously assigned to molecular orbitals that reside primarily in the core of the cluster, [11] this observation does not discount the possibility of significant, surface-localized reactions.R egime II shows an extended period of nanocrystal growth with astrong correlation to the amount of P(SiMe 3 ) 3 added to the solution. During this period, nanocrystal polydispersity was maintained as indicated by the change in full width at half maximum (FWHM) of the excitonic transition ( Figure S2).…”
mentioning
confidence: 95%
“…[12,[18][19][20] Theexistence of nonclassical cluster intermediates during crystal growth has been shown to have profound implications on the growth kinetics of NCs. [23] Specifically,c lose examination of ar ecently discovered InP magicsized cluster,I n 37 P 20 (O 2 CR) 51 , [11] reveals ah igh-symmetry In 13 P 14 core fragment displaying as tructure of multiple polytwistane units helically intersecting in three dimensions. [7,9,14] This last feature has made magic-sized clusters intriguing synthons for templated nanomaterial synthesis and suggests that exploiting their unique structural properties can facilitate the synthesis of new nanoscale phases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…36 The point of convergence of these works is the surface of the QDs. In contrast to the now well-known surface chemistry of the lead and cadmium chalcogenides nanocrystals (NCs), 7 that of phosphide QDs is much less understood and displays a diversity that does not seem to exist for selenides or sulfides.…”
mentioning
confidence: 99%